POLICY EVALUATION OF REGIONAL EXPANSION AND DETERMINATION REGIONAL BOUNDARIES IN BANTEN AND WEST JAVA PROVINCE - Saputra, Romi (Sosiohumaniora, 2021)
The regional expansion is a way to accelerate development acceleration. In addition, regional expansion is the process of dividing an existing administrative area into two or more new autonomous regions. Regional expansion in Indonesia is carried out based on the Law of the Republic of Indonesia number 9 of 2015 concerning Regional Autonomy and Regional Government as a result of the second amendment to the Law of the Republic of Indonesia Number 23 of 2014. However, in the process of regional expansion in Indonesia, there are still some problems. Therefore, this study aims to evaluate government policies in regional expansion and determine regional boundaries in the provinces of Banten and West Java based on the laws in force in Indonesia. The method used in this research is the mix method, namely quantitative and qualitative. The data used are obtained from references and interviews related to regional autonomy policies, regional governments, and the determination of regional boundaries. The results of the evaluation, there are several factors that cause regional expansion, namely religious differences, ethnic and cultural differences, inequality in economic development in an area, and the size of the area. The formation of regional boundaries is carried out through 4 stages, namely Allocation, Delimitation, Demarcation, and Administration. One very important aspect of the implementation of regional autonomy is to merge regions with the hope of strengthening the relationship between local governments and local communities. In addition, it is hoped that there will be more intensive interaction between the community and the new local government, civil society will get better rights and obligations as citizens.